Description of the immature stages of Kuwanina betula Wu & Liu, with a discussion of its placement in the Acanthococcidae family group (Hemiptera: Coccoidea) - Wu, San-An; Nan, Nan (Zootaxa, 2015)
The immature stages of Kuwanina betula Wu & Liu are described and illustrated. Based on morphological and molecular data (18S and 28S rDNA), it is argued that K. betula is closer to Pseudochermes Nitsche than to Kuwanina Cockerell in Fernald and so this species is transferred to Pseudochermes as P. betula (Wu & Liu) comb. nov..